Effect of transplanting period on the population dynamics, parasitism and damage of lepidopteran rice stem borers in irrigated rice scheme of Vallée du Kou, Burkina Faso. (19th January 2015) - Sama, Karim; Nacro, Souleymane; Dakouo, Dona
Abstract : This study was conducted on both station and farmers' fields during the 2010 dry cropping season in the Vallée du Kou rice scheme. We investigated the effect of three rice-transplanting periods (8–10 days) on the population dynamics, damage and parasitism associated with rice stem borers. The on-station experiment was designed as a randomized complete block with three treatments (planting dates) and four replications. Regular intervals of 14 days were observed between subsequent planting dates. Weekly agronomic and entomological assessments were performed from the 21st day after transplanting (DAT) to the 84th DAT. The on-farm experiment covered 1200 ha divided into two zones in which 48 farmers' fields were selected according to the periods of rice transplanting (resulting in 16 fields per period). On-station results indicated 10.1% of deadhearts and 7.5% of whiteheads due to stem borers in the first transplanting period, resulting in the lowest yield (2 metric tons/ha). In farmers' fields, the genus Chilo was found to be the most injurious rice stem borer in Vallée du Kou. The highest larval parasitism (38.5%) was recorded in the third treatment. These results provide important data that can be used in the development of an integrated management strategy for rice insect pests in Vallée du Kou.